Implementasi Metode Depth First Search pada Game Edukasi Matematika RPG 2D untuk Sekolah Dasar - Nur Budi Nugraha; Gellysa Urva; Tri Yuliati (Jurnal Teknologi Komputer dan Informasi, 2026)
The development of digital technology has encouraged the use of educational games as interactive learning media to increase elementary school students’ interest in learning, especially in mathematics subjects which are often considered difficult and monotonous. However, most educational games have not implemented search algorithms to create more interactive gameplay. This study aims to develop a 2D RPG-based mathematics educational game by implementing the Depth First Search (DFS) algorithm to support game navigation and branching story paths. The research used the Research and Development (R&D) method with the Game Development Life Cycle (GDLC) model consisting of the stages of concept, design, production, testing, release, and post-release. Data collection methods included literature studies, observations, and interviews. The DFS algorithm was implemented to determine gameplay paths based on players’ answers to mathematics questions. System testing was conducted using Black Box Testing and questionnaires distributed to 25 elementary school students. The results showed that all game features functioned according to system requirements, and most respondents gave positive responses regarding the game’s appearance, interactivity, and usefulness as a mathematics learning medium. Therefore, the 2D RPG mathematics educational game implementing the DFS method is considered capable of increasing students’ motivation and interest in learning mathematics interactively